Empowerment or legitimation? The Angolan Conselhos de Auscultação e Concertação Social - Hueso González, Andrés (Revista Iberoamericana de Estudios de Desarrollo)
The Conselhos de Auscultação e Concertação Social (CACS) of Angola are spaces of participatory governance, where local authorities have to consult and be accountable to society. Despite limitations in the creation, design and implementation of these spaces, they have great potential for transformation, as they institutionalize the participation of society in local governance. Power dynamics determine to what extent the CACS are participatory and the relevance of the processes of change they open up. Therefore, the social stakeholders should seize the opportunity of political dialectics engaging critically with the CACS.The study contributes to understanding the dynamics, challenges and opportunities arising around the CACS. In general, it highlights the importance of examining the different types of power and deepening in the local context and dynamics when you are studying participatory spaces of local governance.